A map traceability management scheme for security control. Issue 3 (15th March 2020) - Fang, Liguo; Fu, Zhengxin; Yi, Cheng; Zhang, Yong
ABSTRACT: A map traceability management scheme for security control is proposed utilising visual cryptography and Quick Response Code. The map information is classified into two categories: the public information MPI and the traceable map information MTI, and they are both converted into QR codes. Map shares MS and control shares CS are generated according to extended multiple visual cryptographic scheme. MPI can be obtained by scanning the MS, while MTI can be got by overlaying the MS on CS which is only accessible to management units, so it can identify every map and provide the basis for the traceability management.